Uji Validitas Konstruk Skala Lingkaran Pertemanan di Tempat Kerja pada Populasi Indonesia - Baquandi Lutvi Yoseanto (CV. ALIM'SPUBLISHING, 2026)
This study aims to validate the Workplace Friendship Scale (WFS) developed by Nielsen, Jex, and Adams (2000) in the Indonesian population. The WFS measures two dimensions of workplace friendship: Friendship Opportunity (FO) and Friendship Prevalence (FP). A total of 210 employees from various organizations in Indonesia participated in this study. Confirmatory Factor Analysis (CFA) was conducted to examine the construct validity of the scale. The initial two-factor model did not meet the goodness-of-fit criteria (CFI = 0.876; TLI = 0.842; RMSEA = 0.080). After modification by removing problematic items and dimensions, the final model with one factor (Friendship Prevalence) consisting of four items showed acceptable fit (CFI = 0.964; TLI = 0.893; SRMR = 0.031). The reliability coefficient for the final scale was adequate (Cronbach's alpha = 0.794; AVE = 0.497). The results suggest that the modified WFS with four items measuring Friendship Prevalence is a valid and reliable instrument for measuring workplace friendship in the Indonesian context.